Plotting Persuasive Progress in Biblical Hebrew Language Learning: Online Students’ Performance in Bible Online Learner - Winther-Nielsen, Nicolai (HIPHIL Novum, 2022)
Bible Online Learner (https://bibleol.3bmoodle.dk/) claims to deliver a text that can persuade a language learner to practice best online. This corpus-driven learning technology was created as the engine and dashboard to drive learners through four crucial steps in a persuasive technology and design for language learning. The first step is to reduce challenges of learning through instant feedback on practice and to reward the learner with ongoing assessment of progress. The second step is to design for effective and efficient learning by forcing students to follow a specific path through tasks under surveillance of performance. This case is made for learning to read the Hebrew Bible through course material delivered at the My Biblical Hebrew Moodle website (https://mbh.3bmoodle.dk/). The third step is to enhance learning through adaptive tailoring to the need of learners who monitor their own practice. We discuss rich empirical evidence on daily online progression that documents self-directed learning. We have not yet reached the fourth and final step in a persuasive online language learning system, but we believe that it should include social experience from intensive courses, peer-based collaborative learning and enrichment by exposure to a use of modern Hebrew in Israel.